Evolution of grain microbiota during hermetic storage of corn (Zea mays L.) - Marcos Valle, Facundo (2021)
Respiration of biotic components of the grain ecosystem generates self-modified atmospheres (oxygen reduced and carbon dioxide enriched) during hermetic storage. The effect of temperature, moisture content and modified atmospheres on the evolution of maize microbiota is not entirely known. In this study, corn grain samples were conditioned to different moisture contents (14.3, 16.5 and 18.4%) and hermetically stored in glass jars at 15, 25 and 35 °C. Grain samples were collected at different stages of modified atmosphere evolution of each experiment: T0 (O2: 21% initial concentration); T1 (O2: 10%); T2 (O2: 0%); T3 (CO2 maximum concentration stabilized). Microbiota was quantified with Petri dish counts using selective growth media for different microbial groups. Additionally, ethanol, acetic acid and lactic acid were measured for monitoring anaerobic activity. Results indicated that there was a high correlation between water activity (aw) and the time to reach anaerobiosis (R2 of 0.85), the maximum CO2 concentration (R2 of 0.86), and the reduction of filamentous fungi and bacterial counts during hermetic storage (R2 of 0.72 and 0.48, respectively). A differential behavior of the hermetic storage was observed according to aw of the grain, and a general conceptual model is offered for its understanding. It was concluded that modified atmospheres reduced or inhibited microbial growth in stored corn, and that aw was the most influential factor in the time to reach anaerobiosis, maximum CO2 concentration, and the filamentous fungi and bacterial counts reduction during hermetic storage.